Serum and urine electrolyte and nitrogenous waste product changes during the renal functional reserve test (2026)
Context: Renal functional reserve (RFR) refers to the kidney’s capability to increase its basal glomerular filtration rate (GFR) by at least 20 % after an adequate stimulus, such as a protein overload. As far as we know, no studies have yet reported the behavior of electrolyte excretion during the renal functional reserve test. Material and methods: A prospective study to evaluate serum and urinary changes in electrolytes, nitrogenous waste products, glucose, protein, and albumin during the renal functional reserve test in healthy young adults, evaluating their cimetidine-aided creatinine clearance and renal functional reserve test (Hellerstein). Results: There was a statistically significant increase in glomerular filtration rate (positive renal functional reserve) and serum glucose, as well as a significant reduction in serum values of nitrogen derivatives and electrolytes in 46 healthy young adult volunteers during the renal functional reserve test. Regarding the urinary fractional excretion of these substances, significant increases were observed for nitrogenous waste products and electrolytes, except for phosphorus, glucose, protein, and albumin urinary excretion, which suffered no change. Conclusion: The renal functional reserve significantly modified not only glomerular filtration rate but also nitrogenous waste products and electrolyte serum levels, as well as their urinary fractional excretion values in healthy young adults (mean age: 35 years).